2014
DOI: 10.1088/0004-637x/787/1/47
|View full text |Cite
|
Sign up to set email alerts
|

A STUDY OF THE SHORTEST-PERIOD PLANETS FOUND WITHKEPLER

Abstract: We present the results of a survey aimed at discovering and studying transiting planets with orbital periods shorter than one day (ultra-short-period, or USP, planets), using data from the Kepler spacecraft. We computed Fourier transforms of the photometric time series for all 200,000 target stars, and detected transit signals based on the presence of regularly spaced sharp peaks in the Fourier spectrum. We present a list of 106 USP candidates, of which 18 have not previously been described in the literature. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
241
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(269 citation statements)
references
References 86 publications
23
241
5
Order By: Relevance
“…The discovery of a second planet in a grazing configuration, initially missed by automatic pipelines, corroborates the previously observed trend that USP planets are often found in multi-planet systems (Sanchis-Ojeda et al 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The discovery of a second planet in a grazing configuration, initially missed by automatic pipelines, corroborates the previously observed trend that USP planets are often found in multi-planet systems (Sanchis-Ojeda et al 2014).…”
Section: Discussionsupporting
confidence: 87%
“…The same study supports a similar hypothesis in which the progenitors of USP planets are not the HJs but the so-called mini-Neptunes, i.e., planets with rocky cores and hydrogen-helium envelopes, typically with radii between 1.7 and 3.9 R Å and masses lower than ∼10 M Å . An origin of USP planets as photo-evaporated mini-Neptunes is also consistent with the lack of planets with radii between 2.2 and 3.8 R Å with incident flux higher than 650 times the solar constant (Lundkvist et al 2016), the gap between 1.5 and 2 R Å in the population of planets with periods shorter than 100 days (Fulton et al 2017), and the multiplicity of USP planets, typically found with small companions at longer periods (Sanchis-Ojeda et al 2014). While observations of known HJs have confirmed the stability of their atmospheres against evaporation (starting from Vidal-Madjar et al 2003), and theory has always struggled to explain the strong photoevaporation that HJs should undergo to become USP planets (e.g., Murray-Clay et al 2009), removing the outer envelope of a mini-Neptune is theoretically less challenging and several models have successfully reproduced the properties of observed USP planets using either photo-evaporation (e.g., Lopez 2017) or improved models for Roche lobe overflow (e.g., Jackson et al 2017), in agreement with observations of mini-Neptunes undergoing evaporation (Ehrenreich et al 2015).…”
Section: Introductionsupporting
confidence: 68%
“…These catalogs provide timely updates of new, interesting individual objects suitable for ground-based follow-up, and the necessary data for planet occurrence rate calculations as a function of radius, orbital period, and other properties (e.g., Youdin 2011;Catanzarite et al 2011;Howard et al 2012;Morton 2012;Dong et al 2013;Dressing et al 2013;Mulders et al 2014). Independent groups have constructed their own catalogs (Petigura et al 2013;Sanchis-Ojeda et al 2014;Schmitt et al 2014), and derive their own occurrence rates . The comparison of these independent efforts will help identify and correct the inevitable insufficiencies that any approach will suffer for a data set of this size and richness.…”
Section: Introductionmentioning
confidence: 99%
“…While it is unclear how USPs form and how they end up so close to the star, there are several observational clues: systems with USPs commonly host additional planets, which might have played a role in their formation and/or migration histories. Moreover, Sanchis-Ojeda et al (2014) measured a sharp decrease in the occurrence of USPs at radii larger than ∼1.4 Å R and noted a complete lack of USPs at >2.0 Å R . Lopez (2016) showed that the observed dearth of USPs at R p =2-4 Å R suggests that they formed with water-poor H/He envelopes that were subsequently lost via photoevaporation.…”
Section: Introductionmentioning
confidence: 96%